(untitled) (Contextos: Estudios de Humanidades y Ciencias Sociales, 2018)
The present study looks into the concept of myth from the theory of historical knowledge to be included, with his own meaning and value, in the reconstruction of historical western memory and ancient Greece. Its epistemological status is approached distinguishing different uses and meanings, to later approach it inside the Greek ancient experience in the light of Hesíodo’s poetry. We propose, in this sense, the possible rationality of myth as particular human expression with a voice, a meaning and an own historicity, which singularity is outlined by a multitude of convergent features of social and mental structure particular of the Greek period and the diverse contemporary interpretations of the studied phenomenon.